ActiveInk: (Th)inking with Data - Romat, Hugo; Henry Riche, Nathalie; Hinckley, Ken; Lee, Bongshin; Appert, Caroline; Pietriga, Emmanuel; Collins, Christopher (2019 CHI Conference on Human Factors in Computing Systems, 2019)
Watch the video! During sensemaking, people annotate insights: underlining sentences in a document or circling regions on a map. They jot down their hypotheses: drawing correlation lines on scatterplots or creating personal legends to track patterns. We present ActiveInk, a system enabling people to seamlessly transition between exploring data and externalizing their thoughts using pen and touch. ActiveInk enables the natural use of pen for active reading behaviors, while supporting analytic actions by activating any of these ink strokes.
Best Paper Honorable Mention